Photobiomodulation therapy increases neural stem cell pool in aged 3xTg-AD mice - Kevin J. Johnson; Kathia Johnson; Auston Grant; Giulio Taglialatela; Maria-Adelaide Micci (PLoS ONE, 2025)
Presently approved Alzheimer’s Disease (AD) therapeutics are designed for targeted removal of the AD-related toxic protein aggregate amyloid-β (Aβ) and have only shown moderate efficacy at slowing disease progression. Reversal of cognitive decline requires both removal of toxic aggregates and repair of the cellular systems damaged by decades of exposure to these aggregates. Adult hippocampal neurogenesis (AHN) is one such system that is known to be affected early and severely in the development of AD. Moreover, preserved AHN is associated with cognitive resilience to AD neuropathology. Therefore, targeted therapies to improve or enhance neurogenesis should be considered in addition to the removal of toxic protein aggregates. Photobiomodulation (PBM) using 670 nm LED light has been shown to induce synaptic resilience to and removal of AD-related toxic protein aggregates. In this study, we aimed to assess the effect of PBM on a mouse model of advanced AD neuropathology. Transgenic 3xTg-AD mice (15- to 17-month old) were randomized to receive PBM or SHAM therapy for one month, followed by neuropathological assessments. Our results show that one month of PBM therapy reduces hyperphosphorylated tau burden and partially rescues AHN in aged 3xTg-AD mice as compared to SHAM-treated transgenic mice. These data support the notion that PBM has the potential to be an effective non-invasive therapy to help preserve AHN and reduce cognitive dysfunction in moderate to advanced AD.